Bismuth selenide / carbon dot composite negative electrode material and preparation method and application thereof
The nanoscale bismuth selenide/carbon dot composite material was constructed by solvothermal method, which solved the problem of volume expansion and low conductivity of bismuth selenide negative electrode material, and achieved high capacity and good cycling performance of lithium-ion battery negative electrode material.
Patent Information
- Application Number
- CN202510949151.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-08-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery negative electrode material bismuth selenide has problems such as volume expansion leading to electrode structure collapse and low conductivity during charging and discharging, which limits its application in electric vehicles and other fields.
Nano-scale bismuth selenide/carbon dot composite material is constructed by a one-step solvothermal method, and the carbon quantum dots are closely attached to the bismuth selenide nanosheets, shortening the diffusion path of lithium ions and enhancing conductivity and structural stability.
It significantly improves the lithium storage performance and cycle stability of the negative electrode materials of lithium-ion batteries, significantly improves the capacity, and has better circulation performance than existing bismuth selenide-based materials.
Smart Images

Figure CN120440846A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanocomposite electrode materials, and in particular to a bismuth selenide / carbon dot (Bi2Se3 / Carbon dots) composite negative electrode material and a preparation method and application thereof. Background Art
[0002] Energy shortage and environmental pollution have made the development and research of sustainable, renewable and efficient electrochemical energy storage systems one of the most important research areas in the world today.
[0003] Lithium-ion batteries (LIBs) have the advantages of high energy density, long cycle life, and no memory effect, and have received widespread attention in fields such as electric vehicles and smart grids.
[0004] Electrode materials are the key core components that determine the performance of lithium-ion batteries. Their low specific capacity and poor cycle and rate performance are the main obstacles restricting the large-scale application of LIBs in fields such as electric vehicles.
[0005] Currently, commercial LIBs anode materials generally use graphite, whose theoretical capacity is only 372 mAh g -1 Therefore, designing and developing high-performance lithium-ion battery anode materials is an urgent task in current LIBs research.
[0006] Among alternative LIB anode materials, bismuth selenide (Bi2Se3) is a conversion-alloy type anode material with a layered structure and high theoretical capacity. As a two-dimensional layered material, bismuth selenide exhibits remarkable thermoelectric and photoelectric properties, as well as good bioactivity and biocompatibility, making it a promising candidate for lithium-ion battery anodes.
[0007] Bismuth selenide comes in a variety of shapes: Clustered bismuth selenide: 202010970670.1 (publication number CN112281183A) discloses a clustered bismuth selenide, the preparation method of which is: mixing a bismuth salt, selenium dioxide and water, adding a reducing agent solution, wherein the reducing agent is one of hydrazine hydrate and sodium borohydride, heating to 120-200 ° C for a hydrothermal reaction, and synthesizing clustered bismuth selenide by a solvothermal method.
[0008] Nanosheet-structured bismuth selenide: 202210548809.2 (publication number CN114835091A) discloses a nanosheet-structured bismuth selenide, the preparation method of which is as follows: (1) dissolving bismuth nitrate pentahydrate and sodium selenite in an organic solvent (ethylene glycol) and stirring for 30 minutes; (2) adding ascorbic acid to the resulting solution and stirring for 5-10 minutes; (3) charging the reaction solution obtained in step (2) into a reactor, reacting at a constant temperature for a period of time, then cooling to room temperature, collecting by suction to obtain a black-gray precipitate, and repeatedly washing with deionized water and ethanol 2-3 times and drying. The bismuth selenide prepared by this method has a hexagonal crystal structure.
[0009] However, there are two challenges in the application of bulk Bi2Se3 in lithium-ion batteries: First, severe volume expansion occurs during the charge and discharge process, causing the electrode structure to collapse, leading to battery capacity decay and reduced cycle stability; Second, the intrinsic conductivity is low, resulting in poor reaction reversibility and rate performance, which greatly limits the practical application of such materials.
[0010] To this end, researchers have proposed two modification strategies: structural design and component regulation. One strategy involves shortening the ion diffusion path through nanosizing to provide abundant electrochemical active sites, and the other involves improving the conductivity of the material through carbon composites to alleviate volume expansion during charge and discharge, thereby enhancing the electrochemical performance of the electrode material. Nitrogen-doped porous carbon fibers encapsulating bismuth nanoparticles: 202110261796.6 (CN113161530A) describes bismuth-based nanomaterials containing bismuth nanoparticles and nitrogen-doped porous carbon fibers that encapsulate the bismuth nanoparticles. These one-dimensional nanofibers, with a diameter of 150-250 nm, uniformly encapsulate nanoparticles with a particle size distribution of approximately 20 nm.
[0011] Carbon nanofiber negative composite material: (201510299380.8, publication number CN105024050A), obtained by reacting a bismuth salt with small molecule elemental selenium deposited in carbon nanofibers with a three-dimensional network structure and in-situ growth of bismuth selenide; the carbon nanofibers with a three-dimensional network structure are obtained by activating polypyrrole fibers prepared by a template method at a high temperature of 600-1200°C with potassium hydroxide.
[0012] Bi3Se4 particles protected by hollow porous carbon rods: 202210676789.7 (publication number CN114759188A) Bi3Se4 particle potassium electrocomposite material protected by hollow porous carbon rods; Reduced graphene oxide / bismuth selenide composite material, 202410119587.1 (CN117923437A) The present invention uses a simple secondary hydrothermal method to prepare a reduced graphene oxide / bismuth selenide composite material. By coating with reduced graphene oxide, the conductivity of bismuth selenide is increased, and the transmission of zinc ions inside the positive electrode is promoted.
[0013] Carbon quantum dots, or carbon dots for short, are a type of zero-dimensional carbon nanomaterial. They have attracted considerable attention due to their ease of synthesis and unique physical and chemical properties.
[0014] Hybridizing carbon quantum dots as nanofillers with other LIBs anode materials can not only increase the specific surface area of the material and improve the conductivity of the material, but also provide a large number of lithium storage active sites and overcome the volume expansion problem during cycling.
[0015] However, when combining carbon quantum dots and bismuth selenide, either too low or too high a carbon quantum dot content can lead to a decrease in the reversible capacity of the composite material. Specifically, too low a carbon quantum dot content is insufficient to promote electron conduction, resulting in a reduction in reversible capacity, while an excess of carbon quantum dots reduces the proportion of bismuth selenide active material, resulting in a decrease in reversible capacity. Optimizing the carbon quantum dot content in the composite material is crucial to improving the electrochemical performance of the electrode material.
[0016] Therefore, it is expected that the lithium storage performance of bismuth selenide negative electrode materials can be significantly improved by constructing nano-scale bismuth selenide / carbon dot composite negative electrode materials. Summary of the Invention
[0017] The carbon quantum dot content affects the electrochemical performance of the material. Optimizing the carbon quantum dot content is crucial to achieving a composite nanomaterial with optimal electrochemical performance. This invention aims to provide a Bi2Se3 / Carbon Dot composite anode material and its preparation method.
[0018] The first purpose of the present invention is to provide a bismuth selenide / carbon dot composite negative electrode material, the raw materials of which include: carbon quantum dots, bismuth salt, selenite, a reducing agent, and an organic solvent.
[0019] Among the above raw materials: The diameter of the carbon quantum dots is 2-10 nm; The ratio of the carbon quantum dots, bismuth salt and selenite is (10-20) mg: (0.5-2) mmol: (1.0-2.0) mmol, Preferably, the ratio of the carbon quantum dots, bismuth salt and selenite is (10-20) mg: (0.5-1.5) mmol: (1.0-1.5) mmol; Further preferably, the ratio of the carbon quantum dots, bismuth salt and selenite is (15-20) mg:0.8 mmol:1.2 mmol; More preferably, the ratio of the carbon quantum dots, bismuth salt and selenite is 15 mg: 0.8 mmol: 1.2 mmol.
[0020] The molar ratio of the selenite to the reducing agent is (1.0-2.0) mmol: (1.0-2.0) mmol, preferably 1.2 mmol: (1.0-2.0) mmol, and more preferably 1.2 mmol: 1.4 mmol.
[0021] The amount of the organic solvent used is (10-20) mg: (20-40) ml according to the mass volume ratio of carbon quantum dots to organic solvent. Preferably, the mass volume ratio of carbon quantum dots to organic solvent is (10-20) mg: (27.5-32.5) ml. More preferably, the mass volume ratio of carbon quantum dots to organic solvent is 15 mg: 30 ml.
[0022] The bismuth salt is bismuth nitrate pentahydrate (Bi(NO3)3·5H2O), bismuth trichloride (BiCl3), or bismuth citrate (C6H5BiO7); preferably, the bismuth salt is bismuth nitrate pentahydrate (Bi(NO3)3·5H2O).
[0023] The selenite is sodium selenite.
[0024] The reducing agent is L-ascorbic acid (C6H8O6), hydrazine hydrate (N2H4·H2O), or hydroxylamine (H3NO). Preferably, the reducing agent is L-ascorbic acid (C6H8O6).
[0025] The organic solvent is ethylene glycol, ethanol, or dimethylformamide, preferably ethylene glycol.
[0026] The mass and volume used in the present invention can be adjusted by corresponding multiples, such as mg, g, kg, ml, L, etc. For example, the ratio of carbon quantum dots, bismuth salt, and selenite is (10-20) mg: (0.5-2) mmol: (1.0-2.0) mmol, which can be adjusted to (10-20) g: (0.5-2) mol: (1.0-2.0) mol.
[0027] A second object of the present invention is to provide a method for preparing a bismuth selenide / carbon dot composite negative electrode material, the method comprising the following steps: (1) dispersing carbon quantum dots in an organic solvent to obtain a carbon quantum dot solution; (2) adding a bismuth salt dissolved in an organic solvent to a carbon quantum dot solution, and then adding the solution to an organic solvent containing sodium selenite; (3) Add a reducing agent to the reaction solution of step (2), react in a high-pressure reactor, and centrifuge to obtain the product.
[0028] In the above method: The step (1): The carbon quantum dots were ultrasonically dispersed in an organic solvent to obtain a carbon quantum dot dispersion with a concentration of 2 mg / ml; Step (2): The bismuth salt dissolved in the organic solvent has a concentration of 0.03-0.20 mmol / ml, preferably 0.10-0.16 mmol / ml.
[0029] Too high or too low a concentration of bismuth salt will affect the crystal nucleation rate, as well as the size and morphology of bismuth selenide nanosheets.
[0030] The concentration of the selenite-containing organic solvent is 0.06-0.10 mmol / ml, preferably 0.08-0.10 mmol / ml.
[0031] Add bismuth salt dissolved in an organic solvent to the carbon quantum dot dispersion and stir for 4-8 h.
[0032] After adding the organic solvent solution containing selenite, the stirring time is 0.5-1.5 h.
[0033] In step (3): After adding the reducing agent, stir for 0.5-1.5 h.
[0034] The reaction conditions of the high-pressure reactor are: 140-200 °C, reaction time 10-20 h.
[0035] Among the reaction conditions, too low a temperature can affect the crystallinity of bismuth selenide. Furthermore, the boiling point of ethylene glycol is 197°C, so too high a temperature is unsuitable and unsafe.
[0036] After centrifugation in step (3), the method further comprises: washing the precipitate with methanol, then washing with deionized water, and freeze-drying.
[0037] The freeze-drying temperature is -50-70 ℃.
[0038] The carbon quantum dots described herein can be purchased commercially or prepared by the following method: ultrasonically disperse 0.15 g of 1,3,6-trinitropyrene in 0.24 mol / L sodium hydroxide solution. The mixture is then transferred to a 50 ml autoclave, heated to 180°C, and reacted for 12 hours. After cooling to room temperature, the black solution is dialyzed for 3 days and freeze-dried at -60°C.
[0039] The third object of the present invention is to use the bismuth selenide / carbon dot composite negative electrode material to prepare a negative electrode material for a lithium-ion battery, for example, assembling the bismuth selenide / carbon dot composite negative electrode material into a 2032 button-type half-cell.
[0040] The bismuth selenide / carbon dot composite negative electrode material provided by the present invention has the following advantages: 1. In the bismuth selenide / carbon dot composite negative electrode material provided by the present invention, carbon quantum dots are tightly attached to bismuth selenide nanosheets.
[0041] 2. The present invention utilizes a one-step solvothermal method to in situ construct a nano-scale bismuth selenide / carbon dot composite negative electrode material, which can shorten the lithium ion diffusion path, enhance the conductivity of the bismuth selenide negative electrode material and its structural stability during the charge and discharge process, thereby effectively improving the lithium storage performance of the electrode material. Compared with the existing technology, the capacity of the nano-scale bismuth selenide / carbon dot composite negative electrode material prepared by the present invention is significantly improved, and the cycle performance has obvious advantages among the reported bismuth selenide-based materials.
[0042] 3. The present invention has a simple and easy operation process, high reaction efficiency, and is easy to scale up and industrialize. The material has excellent lithium storage performance and is expected to be used as a negative electrode material for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 : X-ray diffraction (XRD) pattern of the bismuth selenide / carbon dot composite negative electrode material prepared in Example 1.
[0044] Figure 2 : Scanning electron microscope (SEM) image of the bismuth selenide / carbon dot composite negative electrode material prepared in Example 1.
[0045] Figure 3 : X-ray energy spectrum (EDS) element distribution diagram of the bismuth selenide / carbon dot composite negative electrode material prepared in Example 1.
[0046] Figure 4 The bismuth selenide / carbon dot composite negative electrode material prepared in Example 1 is used as a negative electrode material for lithium ion batteries at a current density of 100 mA·g -1 In the cycling performance diagram below, the arrows point to the Coulomb efficiency shown on the right vertical axis with the five-pointed star data.
[0047] Figure 5 : Scanning electron microscope (SEM) image of pure bismuth selenide nanomaterial prepared in Comparative Example 1.
[0048] Figure 6 :Comparative Example 1 prepared pure bismuth selenide nanomaterials used as negative electrode materials for lithium ion batteries at a current density of 100 mA·g -1 In the cycling performance diagram below, the arrows refer to the coulombic efficiency shown on the right vertical axis with the five-pointed star data. DETAILED DESCRIPTION
[0049] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0050] The diameter of the carbon quantum dots is 2-5 nm, and the carbon quantum dots can be purchased on the market.
[0051] Example 1: A bismuth selenide / carbon dot composite negative electrode material 15 mg of carbon quantum dots were ultrasonically dispersed in 7.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0052] 0.39 g of bismuth nitrate pentahydrate was dissolved in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion and the mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.25 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, it was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final product, the bismuth selenide / carbon dot composite anode material.
[0053] Example 2: A bismuth selenide / carbon dot composite negative electrode material 10 mg of carbon quantum dots were ultrasonically dispersed in 5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0054] 0.39 g of bismuth nitrate pentahydrate was dissolved in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion and the mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.25 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, it was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final product, the bismuth selenide / carbon dot composite anode material.
[0055] Example 3: A bismuth selenide / carbon dot composite negative electrode material 20 mg of carbon quantum dots were ultrasonically dispersed in 10 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0056] 0.39 g of bismuth nitrate pentahydrate was dissolved in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion and the mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.25 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, it was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final product, the bismuth selenide / carbon dot composite anode material.
[0057] Example 4: A bismuth selenide / carbon dot composite negative electrode material 15 mg of carbon quantum dots were ultrasonically dispersed in 7.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0058] 0.39 g of bismuth nitrate pentahydrate was dissolved in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion and the mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.18 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, it was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final bismuth selenide / carbon dot composite anode material.
[0059] Example 5: A bismuth selenide / carbon dot composite negative electrode material 15 mg of carbon quantum dots were ultrasonically dispersed in 7.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0060] Dissolve 0.39 g of bismuth nitrate pentahydrate in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion. The mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.35 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, the solution was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final bismuth selenide / carbon dot composite anode material.
[0061] Example 6: A bismuth selenide / carbon dot composite negative electrode material 15 mg of carbon quantum dots were ultrasonically dispersed in 7.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0062] Dissolve 0.49 g of bismuth nitrate pentahydrate in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion. The mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.25 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, the solution was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final bismuth selenide / carbon dot composite anode material.
[0063] Example 7: A bismuth selenide / carbon dot composite negative electrode material 15 mg of carbon quantum dots were ultrasonically dispersed in 7.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0064] Dissolve 0.39 g of bismuth nitrate pentahydrate in 5.0 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion and stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.25 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, the solution was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final bismuth selenide / carbon dot composite anode material.
[0065] Example 8: A bismuth selenide / carbon dot composite negative electrode material 15 mg of carbon quantum dots were ultrasonically dispersed in 7.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0066] 0.39 g of bismuth nitrate pentahydrate was dissolved in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion and the mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 12 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.25 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, it was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final product, the bismuth selenide / carbon dot composite anode material.
[0067] Comparative Example 1: Bismuth Selenide Nanomaterial Dissolve 0.39 g of bismuth nitrate pentahydrate in 7.5 ml of ethylene glycol solution, add sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol), stir for 1 hour, and then add 0.25 g of ascorbic acid. After stirring for 1 hour, transfer the mixture to a 50 ml autoclave, heat it to 195°C, and react for 15 hours. After cooling the solution to room temperature, centrifuge it, wash it three times with methanol, wash it twice with deionized water, and freeze-dry it at -60°C to obtain the final product, pure bismuth selenide nanomaterial.
[0068] Comparative Example 2: Bismuth Selenide Nanomaterial (Reactant Concentration Different from Comparative Example 1) (1) Disperse 1 mmol of bismuth nitrate pentahydrate and 1.2 mmol of sodium selenite evenly in 15 ml of ethylene glycol and stir for 30 min. (2) Add 0.25 g of ascorbic acid to the solution prepared in (3) and stir for 1 h; (3) The above solution was transferred to a 50 ml autoclave, reacted at 195 °C for 15 h, cooled to room temperature, centrifuged, washed with methanol three times, washed with deionized water twice, and freeze-dried at -60 °C.
[0069] Comparative Example 3: A bismuth selenide / carbon dot composite negative electrode material (different reaction temperatures) 15 mg of carbon quantum dots were ultrasonically dispersed in 7.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0070] 0.39 g of bismuth nitrate pentahydrate was dissolved in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion and the mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.25 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 130°C and the reaction was continued for 15 hours. After cooling the solution to room temperature, the solution was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final bismuth selenide / carbon dot composite anode material.
[0071] Comparative Example 4: A bismuth selenide / carbon dot composite negative electrode material (different reaction times) 15 mg of carbon quantum dots were ultrasonically dispersed in 7.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0072] 0.39 g of bismuth nitrate pentahydrate was dissolved in 7.5 ml of ethylene glycol solution. This solution was added to the carbon quantum dot dispersion and the mixture was stirred for 6 hours. Then, a sodium selenite solution (containing 0.21 g of sodium selenite in 15 ml of ethylene glycol) was added and stirred for 1 hour. Then, 0.25 g of ascorbic acid was added. The mixture was stirred for 1 hour and then transferred to a 50 ml autoclave. The temperature was raised to 195°C and the reaction was continued for 10 hours. After cooling the solution to room temperature, it was centrifuged, washed three times with methanol and twice with deionized water, and freeze-dried at -60°C to obtain the final product, the bismuth selenide / carbon dot composite anode material.
[0073] Comparative Example 5: A bismuth selenide / carbon dot composite negative electrode material Same as Example 1, except that: 5 mg of carbon quantum dots were ultrasonically dispersed in 2.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0074] Comparative Example 6: A bismuth selenide / carbon dot composite negative electrode material Same as Example 1, except that: 25 mg of carbon quantum dots were ultrasonically dispersed in 12.5 ml of ethylene glycol solution and ultrasonicated for 1 h to obtain a carbon quantum dot dispersion (concentration of 2 mg / ml).
[0075] Experimental Example 1: Comparison of Material Properties 1. Samples: Example 1 and Comparative Example 1.
[0076] 2. Detection method: 2.1 XRD spectrum The X-ray powder diffractometer (XRD, model: Bruker D8 ADVANCE) was used in the scanning range of 10-80° and the scanning speed of 7° min -1 The XRD spectrum of the bismuth selenide / carbon dot composite negative electrode material was collected to study the crystal phase structure of the composite negative electrode material.
[0077] 2.2 SEM images The SEM images of the bismuth selenide / carbon dot composite negative electrode material were collected by scanning electron microscopy (SEM, model: JSM-7001F) to analyze the morphology and microstructure of the composite negative electrode material.
[0078] 2.3 EDS element distribution diagram Energy dispersive X-ray spectrometer (EDS, model) was used to collect EDS element distribution maps of bismuth selenide / carbon dot composite negative electrode materials to analyze the composition of the composite negative electrode materials.
[0079] 3. Experimental results: 3.1 XRD pattern Figure 1 : Figure 1 It shows that the position of the characteristic peak of the product is consistent with the hexagonal phase bismuth selenide standard card, indicating that the bismuth selenide / graphene composite negative electrode material was successfully prepared.
[0080] 3.2 SEM images, see Figure 2 and Figure 5 Figure 2 It can be seen that bismuth selenide has a unique flake-like nanostructure.
[0081] Figure 5 The SEM image of pure bismuth selenide shows that it has a flake-like nanostructure and obvious stacking occurs between the flakes.
[0082] 3.3 EDS element distribution diagram, see Figure 3 (From left to right, from top to bottom are the total distribution of three elements, C, Bi and Se) The figure shows that the three elements C, Bi and Se are evenly distributed in the bismuth selenide / carbon dot composite negative electrode material, among which the C element comes from the carbon quantum dots, confirming that the carbon quantum dots in the composite negative electrode material provided by the present invention are evenly modified on the surface of the bismuth selenide nanosheets.
[0083] Experimental Example 2: Lithium Storage Performance Study 1. Samples: Examples 1-8 and Comparative Examples 1-6.
[0084] 2. Detection method: The bismuth selenide / carbon dot composite negative electrode materials prepared from each sample were assembled into 2032-type button half-cells.
[0085] The working electrode was prepared as follows: 80% (wt) active material (synthesized sample), 10% (wt) conductive carbon black, and 10% (wt) sodium carboxymethyl cellulose binder were thoroughly mixed with an appropriate amount of deionized water. The mixture was then evenly coated on a copper foil and vacuum-dried at 80°C for 8 h. Finally, the mixture was cut into discs with a diameter of 12 mm. The average active material loading on each disc was 1.0-1.2 mg / cm 2. Metal lithium foil was used as the counter electrode and reference electrode, Celgard 2325 microporous membrane was used as the separator, and the electrolyte was a mixed solution of 1.0 M LiPF6 in ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio of 1:1), with 5 wt.% fluoroethylene carbonate (FEC) added. The assembly of the 2032 button half-cell was completed in an argon-filled glove box. The battery test system (model: NEWARE-BTS-4008) was used to test the battery at 0.01-3.0 V ( vs . Li + The cycling performance test of 2032 button half-cell was completed within the voltage range of Li / Li.
[0086] At a current density of 100 mA·g -1 Next, after 30 cycles, test the capacity.
[0087] 3. Experimental results, see Table 1-1, Table 1-2, Figure 4 (Capacity data of Example 1) and Figure 6 (Capacity data of comparative example 1) Table 1-1: Summary of raw material usage and lithium storage performance results of various examples
[0088] Table 1-2: Summary of raw material usage and lithium storage performance results of each example
[0089] The results in Tables 1-1 and 1-2 show that the capacities of Examples 1-8 were 610-680 mAh / g, while those of Comparative Examples 1 and 2 (bismuth selenide materials without carbon quantum dots) were only 90 mAh / g and 80 mAh / g. If the solvothermal reaction temperature was too low (as in Comparative Example 3), the resulting product had a capacity of 300 mAh / g; if the solvothermal reaction time was too low (as in Comparative Example 4), the resulting product had a capacity of 275 mAh / g.
[0090] The results of Experimental Examples 1 and 2 demonstrate that the present invention utilizes a one-step solvothermal method to produce a bismuth selenide / carbon dot composite anode material by adjusting factors such as the carbon quantum dot dosage and reaction temperature. This composite anode material exhibits excellent electrochemical lithium storage performance as a lithium-ion battery anode material. The carbon quantum dots are tightly attached to the bismuth selenide nanosheets.
[0091] In summary, the method of the present invention, through a one-step solvothermal method, in situ constructs a nano-scale bismuth selenide / carbon dot composite negative electrode material, which can shorten the lithium ion diffusion path, enhance the conductivity of the bismuth selenide negative electrode material and its structural stability during the charge and discharge process, thereby effectively improving the lithium storage performance of the electrode material. Compared with the existing technology, the capacity of the nano-scale bismuth selenide / carbon dot composite negative electrode material prepared by the present invention is significantly improved, and the cycle performance has obvious advantages among the reported bismuth selenide-based materials.
[0092] Although the present invention has been described in detail above using general explanations, specific embodiments, and experiments, it will be apparent to those skilled in the art that modifications and improvements may be made based on the present invention. Therefore, such modifications and improvements, which do not depart from the spirit of the present invention, are intended to be within the scope of protection claimed herein.
Claims
1. A bismuth selenide / carbon dot composite negative electrode material, characterized in that: The raw materials of the composite negative electrode material include: carbon quantum dots, bismuth salt, selenite, a reducing agent, and an organic solvent. The diameter of the carbon quantum dots is 2-10 nm, and the ratio of the carbon quantum dots, bismuth salt, and selenite is (10-20) mg: (0.5-2) mmol: (1.0-2.0) mmol.
2. The composite negative electrode material according to claim 1, characterized in that The ratio of the carbon quantum dots, bismuth salt and selenite is (10-20) mg: (0.5-1.5) mmol: (1.0-1.5) mmol.
3. The composite negative electrode material according to claim 1, characterized in that The ratio of the carbon quantum dots, bismuth salt and selenite is (15-20) mg: 0.8 mmol:1.2 mmol.
4. The composite negative electrode material according to claim 1, characterized in that The molar ratio of the selenite to the reducing agent is (1.0-2.0) mmol: (1.0-2.0) mmol.
5. The composite negative electrode material according to claim 1, characterized in that The amount of the organic solvent used is (10-20) mg: (20-40) ml according to the mass volume ratio of carbon quantum dots to organic solvent.
6. The composite negative electrode material according to claim 1, characterized in that The bismuth salt is bismuth nitrate pentahydrate, bismuth trichloride, or bismuth citrate; the selenite is sodium selenite; and the reducing agent is L-ascorbic acid, hydrazine hydrate, or hydroxylamine.
7. The composite negative electrode material according to claim 1, characterized in that The organic solvent is ethylene glycol, ethanol, or dimethylformamide.
8. The method for preparing the composite negative electrode material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: (1) dispersing carbon quantum dots in an organic solvent to obtain a carbon quantum dot solution; (2) adding a bismuth salt dissolved in an organic solvent to a carbon quantum dot solution, and then adding the solution to an organic solvent containing sodium selenite; (3) Add a reducing agent to the reaction solution of step (2), react in a high-pressure reactor, and centrifuge to obtain the product.
9. The preparation method according to claim 8, characterized in that The carbon quantum dots are ultrasonically dispersed in an organic solvent to obtain a carbon quantum dot dispersion with a concentration of 2 mg / ml; the bismuth salt dissolved in the organic solvent has a concentration of 0.03-0.20 mmol / ml; the reaction conditions of the high-pressure reactor in step (3) are: 140-200 °C, and the reaction time is 10-20 h.
10. Use of the composite negative electrode material according to any one of claims 1 to 7 in preparing negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Bismuth selenide / carbon nanofiber composite anode material for sodium ion battery and preparation method thereof
CN105024050A
A bismuth selenide / carbon nanofiber anode composite material for sodium-ion batteries and its preparation method
CN105024050B
Clustered bismuth selenide, preparation method thereof and application of clustered bismuth selenide in electrocatalytic reduction of carbon dioxide
CN112281183A
Clustered bismuth selenide, its preparation method, and its application in the electrocatalytic reduction of carbon dioxide.
CN112281183B
Bismuth-based nano material as well as preparation method and application thereof
CN113161530A
